2008
DOI: 10.1080/00222216.2008.11950155
|View full text |Cite
|
Sign up to set email alerts
|

Recreation Visitor Attitudes Towards Management-ignited Prescribed Fires in the Bob Marshall Wilderness Complex, Montana

Abstract: Research at the Bob Marshall Wilderness Complex in Montana explored differences in recreation visitors' attitudes towards the use of management-ignited prescribed fires in the wilderness. A mail-back survey of visitors (n = 291) during the 2004 season revealed that over half of visitors would accept prescribed fires in wilderness. This support did not vary by ignition purpose: (a) to restore the natural role of fire or (b) to reduce hazardous fuels and potential for fire escaping to non-wilderness lands. Local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Overall, the research paints a picture of a public that often has a sophisticated understanding of how fire fits into the ecosystemin terms of its ecological role as well as the environmental characteristics that contribute to increased fire risk. In qualitative studies, understanding of fire's role in the environment is referenced primarily in two ways: 1) awareness of the risks of living in a natural landscape and perceptions that the current forest is unhealthy from too many trees and/or a buildup of fuel (Brenkert-Smith 2011, Burns and Cheng 2007, Cohn et al 2008, Kent et al 2003, McCaffrey 2008b, Paveglio et al 2011, Weisshaupt et al 2007) and 2) discussions of overall forest management and the need to reintroduce fire, whether via prescribed fire or allowing some naturally ignited fires to burn (Knotek et al 2008, McFarlane et al 2007, Mendez et al 2003, Winter and Cvetkovich 2008.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the research paints a picture of a public that often has a sophisticated understanding of how fire fits into the ecosystemin terms of its ecological role as well as the environmental characteristics that contribute to increased fire risk. In qualitative studies, understanding of fire's role in the environment is referenced primarily in two ways: 1) awareness of the risks of living in a natural landscape and perceptions that the current forest is unhealthy from too many trees and/or a buildup of fuel (Brenkert-Smith 2011, Burns and Cheng 2007, Cohn et al 2008, Kent et al 2003, McCaffrey 2008b, Paveglio et al 2011, Weisshaupt et al 2007) and 2) discussions of overall forest management and the need to reintroduce fire, whether via prescribed fire or allowing some naturally ignited fires to burn (Knotek et al 2008, McFarlane et al 2007, Mendez et al 2003, Winter and Cvetkovich 2008.…”
Section: Resultsmentioning
confidence: 99%
“…In general, studies have found a preference for use of mechanical thinning in more urbanized areas and for prescribed fire in less populated areas (Brunson and Shindler 2004, Knotek et al 2008, McFarlane et al 2007, Paveglio…”
Section: Preferencesmentioning
confidence: 99%
“…As well, public education and outreach has had a positive influence on knowledge about fuel reduction treatment methods [34,35]. Some studies have found respondents accepted the use of prescribed burning as an ecological practice on public land, although they preferred mechanical treatments when the forest is located close to a populated area [32,36,37]. Despite these findings, high knowledge levels have also been associated with decreased concerns [20,38].…”
Section: The Biophysical Contextmentioning
confidence: 99%
“…Although prescribed fire has ecological advantages, a successful fire program for landscape-scale restoration requires public support (Knotek et al 2008;Loomis et al 2001). Attitudes play a critical role in the formation of opinions that can create challenges related to use of prescribed fire for different management activities, including longleaf pine restoration.…”
Section: Background 21 Attitudes Regarding Use Of Prescribed Firementioning
confidence: 99%